Teaching About Hegemony: Race, Class and Democracy in the 21st Century - Stelmach, Bonnie Lynn (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
This is a review of Paul Orlowski's "Teaching About Hegemony: Race, Class and Democracy in the 21st Century." Using Canadian and American contexts as a backdrop for social studies teaching, he argues for critical media literacy and politicization of teachers of social studies. This book is theoretically rich and practically oriented with questions at end of the chapters to prompt further discussion and self-reflection. it is suitable as a conceptual guide and classroom textbook for university educators teaching curriculum/methods in the area of social studies.